POPULATION PROBLEMS IN KOREA, LOW BIRTH RATE, GENDER EQUALITY AND WOMEN'S SOCIAL STATUS - Dilafruz Sobirova (Ta'lim innovatsiyasi va integratsiyasi, 2024)
Аnnotation. This article describes the structure of government in the Republic of  Korea,  as  well  as  the  division,  definition  and  functions  of  local  government. Population problems, low birth rates, gender equality and the social status of women in Korea were also studied.